Columnea rangelii (gesneriaceae), a new species from the serranía de los paraguas in the colombian andes (2012)
A new species of Columnea belonging to the section Collandra (Gesneriaceae) from La Serranía de los Paraguas in the Department of Valle del Cauca (Cordillera Occidental), Colombia, is described and illustrated.